Literature Review : Analysis Implementation of Worksheets Students in Green Chemistry Against Green Chemistry Principles for Students at SMAN 1 Jamblang - Ningsih, Alia Fitria; Mutiara Dwi C; Aneu; Ema Nurhidayah R (Education, Science, and Technology International Conference, 2025)
Study This aiming For analyze Application of Worksheet Students (LKPD) in context learning chemistry green and its influence to understanding green chemistry principles at SMAN 1 Jamblang . With use literature review approach , articles This to study various studies previous about the role of LKPD in increase engagement and results Study students . Results of the analysis show that integrated implementation of LKPD with the principles of green chemistry are able increase understanding student to concepts sustainability and environment . Research This expected can give contribution positive for development method more learning​ effective in education chemistry as well as push sensitivity student to issues environment.